(untitled) (Historia, 2021)
The South Africa helicopter-borne assault on Ongulumbashe in August 1966, a known South West Africa People’s Organisation (SWAPO) base in the north of the then South West Africa, signalled the beginning of the so-called South African "Border War". The conflict lasted for roughly 24 years until 1989. The South African Defence Force (SADF) and the South African Police (SAP) were involved in counterinsurgency operations in the South West Africa from the 1960s when SWAPO categorically decided to use in its quest to gain the independence of Namibia.